Direct Part Marking by Vibration Assisted Face Milling. (2016) - Denkena, Berend; Grove, Thilo; Seibel, Alexander
Abstract: Critical or safety components have to be identified during maintenance especially if exposed to harsh conditions during the time of operation. Direct part marking (DPM) is a process to permanently mark parts with product information such as serial numbers, part numbers, date codes and barcodes. An advanced machining technology is presented (vibration assisted face milling, VAFM), enabling the machining of Data Matrix Codes (DMC) and similar shapes carrying inherent data into the components surface without any additional process step. The technology is based on a piezo-electrically driven milling tool. The dynamics of the tool enable a highly dynamic and controlled depth of cut variation during the cutting process while using process parameters applied in real-life industrial processes. As an example for safety components, the technology is demonstrated on TiAl6V4, one of the most important titanium alloys in the aerospace industry. The machined result is evaluated on the machining quality of the DMC data cells edges and the contrast.